Terrenos de marinha: terras públicas com função social? um estudo da orla marítima de natal - Valença, Daniel Araújo (2010)
This work has as its theme the social function of terrenos de marinha. Theresearch universe is the terrenos de marinha of Natal coastline, focusing on thefulfillment of its social function. Prescribed by law since the colonial period with thepurpose of protecting the coast and free movement of people and goods, theywere swathes of land not available to private use by individuals. With the transitionfrom the allotments system to the purchase and sale, regard to land access,crystallized with the creation of the Land Law in the nineteenth century, the land isheld as merchandise and terrenos de marinha, following this logic, also acquireexchange value and become capable of enjoyment by private individuals, with thecondition of tax payments to the state. This is seen until the twentieth century,when in 1988, primarily because of the Federal Constitution promulgation, begins anew cycle when is possible to use on terrenos de marinha the principle of thesocial function of property. From this perspective this study aims to identify thesocial function of terrenos de marinha in Natal, focusing on the public destinationand the use value of the city coastline. To this end, it was made a data collection inthe on-line information system of the Federal Heritage Department of Rio Grandedo Norte (SPU / RN) and in the terrenos de marinha areas, in order to find out ifthey had public or private use, or if they were empty lots, as well as if thepopulation access to the shore exist. Interviews with managers of the SPU weremade. The empirical study showed that the social function of terrenos de marinhain the city of Natal still didn´t happen, considering the constant existence of vacantlots in their areas, the lack of access in significant portions of the coastline and thereduced areas directed to common use along the coastline, minimizing its potentialof enjoyment by the population. It concludes by pointing to the existence of a newtransition phase on the terrenos de marinha, in witch, gradually, come up lawprovisions in the legal system and public policies to expand the purely taxcollection function attributed to this land for two centuries. In this direction, thesocial function of terrenos de marinha is embodied in concomitant adjustment ofthe tax collection function and the rescue of coastline use value, national heritageand a place for sociability and social relations development